Putting the Public into Public Radio: Web 2.0 Interactivity and RNZ National - Sinton, Maureen (Auckland University of Technology, 2016)
A new relationship paradigm is forming between public radio and its audience, due to the introduction of Web 2.0 technology that allows for the audience to interact easily with the broadcaster, from the platform of their choice. This paradigm contrasts with the traditional model of public broadcasting which provided the audience with a one-way media experience. New Zealand public service broadcaster RNZ National was used as a case study for this research project. Using grounded theory methodology the phenomenon of audience interactivity on public radio was studied from both sides of the microphone meaning that programme makers were interviewed and the contributions by listeners were analysed. Feedback content (comments contributed and read on-air) was recorded across most day-parts. News stories and interviews, as well as the comments of hosts and other listeners, acted as prompts, motivating the audience to engage with the broadcaster. Those topics with an emotional relevance to the audience attracted the most response. RNZ National staff responsible for the creation of content were surveyed for their views on the role of audience interactivity. All staff expressed the view that feedback is now an important component of the network's content. The number of comments broadcast indicates that Web 2.0's interactive technology has been readily adopted by the audience. The conversational tone of much feedback suggests that the audience perceive the host as a friend, and that their interactivity is a communication taking place within a relationship. By incorporating audience interactivity into its programme content, RNZ National has put the public into New Zealand public radio.
Keywords: public radio; public broadcasting; interactivity; talkback; Web 2.0; radio; New Zealand radio; RNZ National